Pengembangan Umkm Berbasis Digitalisasi Desa Sungai Nibung, Kecamatan Siak Kecil, Bengkalis - Susanti, Rina; Syaputra, Indra; Lestari, Fadilah Nike; Muflihatun, Umi; Ziza, Bulan; Amjad, M. Adnan; Aksa, Ramzilas; Suci R.N, Adelya Try Wulan; Nursal, Destalian Bembi; Pratama, Andika Saputra; Afrianza, Ananda; Kurniasih, Cici; Triadi, Rifkiy Maulana (Civiliza Publishing, 2024)
As time progresses, it requires MSMEs to maximize technological developments to be able to compete to attract consumers by promoting products online. With the main target group of MSMEs, this community service is carried out with no other aim than to empower and improve the knowledge and skills of MSMEs in Sungai Nibung Village, Siak Kecil District, Bengkalis Regency, who are found to still have minimal mastery of business digitalization. Thus, online business marketing training and attractive product design, utilization of Google Maps points, creation of village MSME profile books, assistance in creating logos, and business licenses for those who do not have them so that they can advance MSMEs in Sungai Nibung Village. Previously, many MSMEs only marketed their products by word of mouth so that they were not widely known by consumers and the general public. In order to achieve the goal, community service activities were carried out using the participatory rural appraisal (PRA) method combined with practical methods. The result was that the knowledge and skills of the target group increased, and the potential of MSMEs in Sungai Nibung Village was successfully published.